Inskripsi pada Kompleks Makam Raja-raja Mempawah, Kalimantan Barat - Saefullah, Asep (SUHUF, 2012)
The objective of this paper is an examination of the religious inscriptions found in the cemetery of the kings of Mempawah, an Islamic kingdom in Ponti-anak Regency, West Kalimantan. The pioneer research focuses on an inventory and description of field data collected at the graveyard. It documents examples of the inscriptions and their transliterations which are then classified according to the contents and style of calligraphy.